MODERN METHODS OF TEACHING HISTORY - Rustamov Ramziddin (Western European Studies, 2025)
This article analyzes modern pedagogical methods and innovative technologies used in teaching history. It explores the role of constructivist approaches, the application of information and communication technologies (ICT), and the implementation of interactive and project-based learning in shaping students' personalities. The study highlights the impact of these methods on deepening historical knowledge, developing critical thinking, and nurturing active, patriotic citizens committed to national values. The article also provides practical recommendations for updating the content and format of history education in accordance with contemporary educational standards.
Keywords: history education; modern methods; interactive learning